PENGARUH MEDIA PROMOSI KESEHATAN BOOKLET TERHADAP PENGETAHUAN CALON PENGANTIN TENTANG PENCEGAHAN PENULARAN HIV/AIDS DI KANTOR URUSAN AGAMA KECAMATAN WALANTAKA KOTA SERANG BANTEN TAHUN 2024 - Muhida, Vega; Tu’sadiah, Halimah; Musllihah, Liana; Adista, Nuria Fitri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: This study aims to assess the effectiveness of media booklets in enhancing prospective couples' knowledge about HIV/AIDS prevention. HIV/AIDS is a global health issue with 37.9 million people living with the condition, including 1.7 million children under 15 and 36.2 million adults (UNAIDS, 2019). Insufficient knowledge about HIV/AIDS complicates efforts for early detection and control, leading to increased AIDS-related deaths (Ministry of Health of the Republic of Indonesia, 2022; Purnamawati, 2016). Therefore, early detection and diagnosis are crucial for reducing transmission and improving life expectancy. This research employs an experimental method with a pretest-posttest design. The sample consisted of 110 prospective couples who received a media booklet as an intervention. Analysis results indicate that the media booklet significantly improved the prospective couples' knowledge, with a P-value of 0.000. These findings suggest that the media booklet is an effective educational tool, presenting information in a straightforward yet comprehensive manner. This supports previous research highlighting the positive impact of media booklets on health education, reinforcing memory, and clarifying information. The study also aligns with the educational principles in Surah Al-Imran (3:110), emphasizing the importance of conveying goodness and preventing wrongdoing. Based on the study’s results, it is recommended that media booklets be integrated into every counseling and guidance session for prospective couples by the Religious Affairs Office (KUA) and related institutions. Media booklets should be considered a primary strategy in health promotion programs for disease prevention, given their significant impact on improving public health literacy. The outcomes of this study include publication in accredited journals and the application for intellectual property rights (IPR) for the media booklet as a health education tool.Keywords: Booklet, HIV/AIDS Preventio